2016
DOI: 10.1080/15389588.2016.1151011
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing injury severity factors at highway railway grade crossing accidents involving vulnerable road users: A comparative study

Abstract: The ordered probit model was the primary technique, and CART and association rules act as the supporter and identifier of interactions between variables. All 3 algorithms' results consistently show that the most influential accident factors are train speed, VRU age, and gender. The findings of this research could be applied for identifying high-risk hotspots and developing cost-effective countermeasures targeting VRUs at HRGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Although poor illumination may be a contributory factor but it is not a major determinant according to this study. 8 In contrast a German study revealed marked seasonal, weekly and diurnal peaks of railway suicide intensity. Differences between men and women indicate sexspecific processes underlying their suicidal behaviour.…”
Section: Contusion Laceration Contusion Lacerationmentioning
confidence: 92%
“…Although poor illumination may be a contributory factor but it is not a major determinant according to this study. 8 In contrast a German study revealed marked seasonal, weekly and diurnal peaks of railway suicide intensity. Differences between men and women indicate sexspecific processes underlying their suicidal behaviour.…”
Section: Contusion Laceration Contusion Lacerationmentioning
confidence: 92%
“…Ghomi et al [23] applied an ordered probit model, association rules, and classification and regression tree (CART) algorithms to the US Federal Railroad Administration's (FRA) HRGC accident database for the period 2007-2013 to identify VRU injury severity factors at HRGCs. Using six years of nationwide crashes from 2009 to 2014 in the US, Haleem [24] applied both the mixed logit and binary logit models based on the multiple predictors investigation (e.g., temporal crash characteristics, geometry, railroad, traffic, vehicle, and environment).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research studies have focused on roadway intersection or roadway crashes [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Relatively little research effort has focused on HRGC accidents compared to roadway accidents [15][16][17][18][19][20][21][22][23][24]. Moreover, among all the previous HRGC accident analyses, the majority of them focus only either on crash frequency, often based on crossing inventory databases [19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], or on crash severity analysis, often based on historical crash police report databases [16,[40][41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little research effort has focused on HRGC accidents compared to roadway accidents [15][16][17][18][19][20][21][22][23][24]. Moreover, among all the previous HRGC accident analyses, the majority of them focus only either on crash frequency, often based on crossing inventory databases [19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], or on crash severity analysis, often based on historical crash police report databases [16,[40][41][42][43][44][45][46][47][48][49][50][51][52]. To understand and predict crash frequency and severity simultaneously and consistently is important for agencies seeking to improve safety so they can account for the common factors affecting both crash frequency and severity.…”
Section: Introductionmentioning
confidence: 99%